2008
DOI: 10.1182/blood-2007-10-117044
|View full text |Cite
|
Sign up to set email alerts
|

A2B adenosine receptor dampens hypoxia-induced vascular leak

Abstract: IntroductionPrevious studies have implicated extracellular nucleotide metabolites, predominantly adenosine, as triggers of endogenous protective mechanisms in a number of acute injury models. [1][2][3][4][5][6][7] Extracellular adenosine is derived primarily through phosphohydrolysis of adenosine 5Ј-monophosphate (AMP). Ecto-5Ј-nucleotidase (CD73), a ubiquitously expressed ectoenzyme, is the pacemaker of this reaction. 8 Studies on the role of CD73 in tissue-injury showed that cd73 Ϫ/Ϫ mice develop profound va… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

20
332
1
2

Year Published

2009
2009
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 274 publications
(355 citation statements)
references
References 59 publications
20
332
1
2
Order By: Relevance
“…As first step, we induced diabetic nephropathy in previously described Adora2b 2/2 mice. 23,[28][29][30][31][48][49][50][51] Similar to the preceding studies in Cd73 2/2 mice, we observed a more severe degree of diabetic nephropathy in Adora2b 2/2 mice without differences regarding systolic BP and blood glucose levels (Supplemental Figure 4, A and B), but a more severe degree of body weight loss ( Figure 5A), increased kidney weight (Figure 5B), and elevated urine (Figure 5C) and drinking ( Figure 5D) volumes. Determination of the GFR showed a more severe hyperfiltration in Adora2b 2/2 mice compared with diabetic control mice ( Figure 5E).…”
Section: Diabetic Nephropathy Is More Severe In Adora2bsupporting
confidence: 73%
See 1 more Smart Citation
“…As first step, we induced diabetic nephropathy in previously described Adora2b 2/2 mice. 23,[28][29][30][31][48][49][50][51] Similar to the preceding studies in Cd73 2/2 mice, we observed a more severe degree of diabetic nephropathy in Adora2b 2/2 mice without differences regarding systolic BP and blood glucose levels (Supplemental Figure 4, A and B), but a more severe degree of body weight loss ( Figure 5A), increased kidney weight (Figure 5B), and elevated urine (Figure 5C) and drinking ( Figure 5D) volumes. Determination of the GFR showed a more severe hyperfiltration in Adora2b 2/2 mice compared with diabetic control mice ( Figure 5E).…”
Section: Diabetic Nephropathy Is More Severe In Adora2bsupporting
confidence: 73%
“…We had shown in several previous studies that this compound has pharmacologic effects in wild-type or Adora2a 2/2 mice, but not in Adora2b 2/2 mice. 24,31,50,51 For the purpose of our studies, we administered BAY 60-6583 via osmotic pump (0.3 mg per mouse per hour). Indeed, we observed that continuous BAY 60-6583 treatment had no effect on systolic BP or blood glucose levels (Supplemental Figure 6, A and B) but was associated with an attenuated wasting syndrome after STZ treatment ( Figure 8, A-D).…”
Section: Adora2b-mediated Kidney Protection During Diabetic Nephropatmentioning
confidence: 99%
“…In this same study, the pivotal role of the A 2B in attenuating hypoxia-induced increases in vascular leak, mainly in the lungs, was also observed with selective agonists or antagonists of adenosine A 2B receptor in mice or in vitro treatment with siRNA-targeting adenosine A 2B receptor. Furthermore, additional studies suggested a critical role of HIF-1 in the transcriptional induction of the adenosine A 2B receptor during hypoxia [51]. Recently, an interesting study conducted by the same group extended the data described above and revealed an adenosine A 2B receptor-dependent lung protection to ventilation-induced lung injury and LPS-induced lung injury, related to a decrease in pulmonary inflammation, increase in alveolar fluid clearance, reduction in pulmonary edema, and maintenance of capillary-alveolar barrier-a mechanism that involves adenosine A 2B receptor expression with elevation of pulmonary cAMP levels [52].…”
Section: Discussionmentioning
confidence: 99%
“…It is also virtually equipotent with caffeine on most studied isoforms of PDE (45) and less potent than other caffeine metabolites such as theophylline or paraxanthine. The more specific A 2B antagonist PSB1115 (11,12,22,48) had no effect on HR, suggesting that induced PDE inhibition may be important. We also did not observe any changes in Temp following long-term oral caffeine ingestion.…”
Section: ␤-Receptor Blockade By Timolol Is Unlikely As An Explanationmentioning
confidence: 99%
“…In the present study, we have examined caffeine effects in mice that lack either A 1 R or A 2A R or both. We also examined effects of the selective A 2B R antagonists, enprofylline (20,39) and 1-propyl-8-psulfophenylxanthine (PSB1115) (11,22,48). The parameters we examined were heart rate (HR), body temperature (Temp), locomotor activity (LA), and oxygen consumption (O 2 C) since they could be examined in awake animals and for prolonged periods of time.…”
mentioning
confidence: 99%